2012
DOI: 10.3174/ajnr.a2882
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor, Visual, and Auditory Cortical Atrophy in Unverricht-Lundborg Disease Mapped with Cortical Thickness Analysis

Abstract: Cortical thinning in the sensorimotor areas in EPM1 correlated significantly with the degree of the severity of the myoclonus and is most likely related to the widespread stimulus sensitivity in EPM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Heinzel et al 2013 have recently reported that up to 41 % of the variance in the HHb signal and up to 18 % of the variance in the O 2 Hb signal in frontal regions can be explained by individual grey matter volume; moreover, differences in the distance between the scalp and cortex may affect the sensitivity of fNIRS (Haeussinger et al 2011). As in previous studies of EPM1 patients (Koskenkorva et al , 2012, we found that motor area CT was moderately reduced in our patients, and correlated with the reduction in the hemodynamic signals.…”
Section: Movement-related Eeg Changes and Hemodynamicsmentioning
confidence: 80%
“…Heinzel et al 2013 have recently reported that up to 41 % of the variance in the HHb signal and up to 18 % of the variance in the O 2 Hb signal in frontal regions can be explained by individual grey matter volume; moreover, differences in the distance between the scalp and cortex may affect the sensitivity of fNIRS (Haeussinger et al 2011). As in previous studies of EPM1 patients (Koskenkorva et al , 2012, we found that motor area CT was moderately reduced in our patients, and correlated with the reduction in the hemodynamic signals.…”
Section: Movement-related Eeg Changes and Hemodynamicsmentioning
confidence: 80%
“…However, changes in MRI, such as mild to moderate cerebral and/or cerebellar atrophy, loss of neuronal volume in the brainstem and high intensity signal changes in the basal ganglia have been reported as well [7], [10][12]. Recently modern group level MRI analysis methods have revealed loss of gray matter volume in cortical motor areas (voxel-based morphometry, VBM), and atrophy of the sensorimotor, visual and auditory cortices (cortical thickness analysis, CTH) in EPM1 patients [13], [14] while abnormal findings could not be detected in visual assessments. Loss of gray matter volume in the thalamus has also been reported in one VBM study [13], paralleling a PET study indicating dopamine depletion in the thalamostriatal area in four EPM1 patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…A voxelbased morphometry (VBM) analysis revealed atrophy in primary, premotor, and supplementary motor cortices bilaterally . Furthermore, a cortical thickness analysis found that EPM1 patients had thinner sensorimotor, visual and auditory cortices than controls (Koskenkorva et al, 2012). Cortical thickness was shown to correlate negatively with age, duration of EPM1, and clinical severity of myoclonus.…”
Section: Introductionmentioning
confidence: 98%